(untitled) (Research, Society and Development, 2022)
This work discusses the Amazonian challenges regarding education presented by Djalma Batista in an essay entitled “Amazon Culture” and originally published in the "Revista da Academia Amazonense de Letras" in 1955. The objective is to answer the following question: The educational problems of the Amazon pointed out by Djalma Batista in the first half of the 20th century remain the same at the turn of the 21st century? For that, qualitative and bibliographic research was used, and as a source, the base work of Batista, in addition to books, articles, dissertations and theses that deal with Amazonian education at the beginning of the 21st century. It was found that two Amazonian challenges presented by the author remain the same: low salary appreciation and precarious working conditions of the teachers’ class and schools in low-income neighborhoods continue with unsatisfactory and inadequate facilities, the only divergence is in relation to higher education, while at the time of the author there was only a law course, today there are several courses available in both public institutions, as well as in several private ones.